Pain coping, pain acceptance and analgesic use as predictors of health-related quality of life among women with primary dysmenorrhea. (March 2020) - Kapadi, Romaana; Elander, James
Abstract: Objectives: Primary dysmenorrhea causes menstrual pain that affects women's quality of life (QoL) and analgesics are only moderately effective. Pain coping and pain acceptance influence QoL among people affected by other chronic pain conditions, so we examined pain coping, pain acceptance and analgesic use as predictors of QoL among women with primary dysmenorrhea. Study design: 145 women with primary dysmenorrhea completed an online survey including the Menstrual Symptoms Questionnaire (MSQ), the Coping Strategies Questionnaire (CSQ), the Chronic Pain Acceptance Questionnaire (CPAQ-8), questions about analgesic use, and the Short Form-12 (SF-12), a measure of physical and mental health-related QoL. Results: In multiple regression, pain acceptance predicted better physical and mental QoL, whereas pain coping did not predict mental or physical quality of life. Being married or cohabiting and menstrual pain that was less severe and shorter in duration predicted better physical QoL, and those effects were mediated by pain acceptance. Being older at the onset of painful periods predicted better mental QoL and that effect was also mediated by pain acceptance. More severe menstrual pain and congestive rather than spasmodic dysmenorrhea predicted worse mental QoL but those effects were not mediated by other factors. Analgesic use did not predict physical or mental QoL. Conclusions: The results show the impact that menstrual pain has on women's quality of life, and suggest that initiatives to increase pain acceptance among women with menstrual pain are worthwhile. More research is needed to understand more fully the factors that influence health-related quality of life among women with menstrual pain.